2002
DOI: 10.1037/1076-8998.7.2.130
|View full text |Cite
|
Sign up to set email alerts
|

Supportive colleague, unsupportive supervisor: The role of provider-specific constellations of social support at work in the development of low back pain.

Abstract: In a 5-year longitudinal study, social support was investigated as a predictor of low back pain (LBP) in 46 initially asymptomatic individuals. Distinguishing between colleagues in general and the colleague one feels closest to, the authors analyzed constellations of support from supervisor (which had positive effects) and closest colleague (which had detrimental effects). Configural frequency analysis yielded a type characterized by high support from one's closest colleague and low support from one's supervis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 36 publications
(48 reference statements)
2
56
0
Order By: Relevance
“…This is consistent with [5], [6], [13], and [14] study. This indicates that social support from supervisor and co-workers can help academics cope with job stressors.…”
Section: Discussionsupporting
confidence: 82%
“…This is consistent with [5], [6], [13], and [14] study. This indicates that social support from supervisor and co-workers can help academics cope with job stressors.…”
Section: Discussionsupporting
confidence: 82%
“…The answering format was a four-point scale ranging from 1 (not at all) to 5 (absolutely). The scale has been shown to predict occupational LBP before 32) .…”
Section: Candidate Predictor Variables Assessedmentioning
confidence: 99%
“…Few studies in return-to-work research have discussed the notion of workgroup social interaction, although some have indicated that workplace economic and social conditions, attitudes and beliefs may be of significance regarding the outcome of a return-to-work process [14][15][16][17]. To further investigate the experiences and roles of co-workers, there is a need to move beyond present return-to-work models to consider the return-to-work process in its complexity including the nuances of social interaction [3,6,13,18].…”
Section: Introductionmentioning
confidence: 99%